2020
DOI: 10.1515/nleng-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

A generalized perspective of Fourier and Fick’s laws: Magnetized effects of Cattaneo-Christov models on transient nanofluid flow between two parallel plates with Brownian motion and thermophoresis

Abstract: AbstractPresent research article reports the magnetized impacts of Cattaneo-Christov double diffusion models on heat and mass transfer behaviour of viscous incompressible, time-dependent, two-dimensional Casson nanofluid flow through the channel with Joule heating and viscous dissipation effects numerically. The classical transport models such as Fourier and Fick’s laws of heat and mass diffusions are generalized in terms of Cattaneo-Christov double diffusion models by accounti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Viscous dissipation, free convection and axial heat conduction are ignored. Classical Fourier’s law of conduction will become accordingly 26 in the absence of Cattaneo-Christov modelswhere q is the heat flux and κ nf the effective thermal conductivity of nano fluid. Since we have carried out the fully developed fluid flow, 24 so, we have…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Viscous dissipation, free convection and axial heat conduction are ignored. Classical Fourier’s law of conduction will become accordingly 26 in the absence of Cattaneo-Christov modelswhere q is the heat flux and κ nf the effective thermal conductivity of nano fluid. Since we have carried out the fully developed fluid flow, 24 so, we have…”
Section: Problem Formulationmentioning
confidence: 99%
“…Viscous dissipation, free convection and axial heat conduction are ignored. Classical Fourier's law of conduction will become accordingly 26 in the absence of Cattaneo-Christov models…”
Section: Problem Formulationmentioning
confidence: 99%
“…The relations for heat flux q and mass flux j with their respective relaxation factor according to Cattaneo-Christov theory are given as (see Refs. [28,[30][31][32]):…”
Section: Cattaneo-christov Theory Of Heat and Mass Fluxmentioning
confidence: 99%
“…They announced that thermal boundary layer thickness of Carreau liquid with C-C double diffusion is smaller in contrast to Carreau liquid implementing the Fourier's law. Literature search revealed that recently many other researchers [28][29][30][31][32] have also used Cattaneo-Christov model to inspect heat and mass movement.…”
Section: Introductionmentioning
confidence: 99%
“…It is noticed from their analysis that, the Blasius ow gives the thicker temperature boundary layer when compared to the Sakiadis ow. Usha et al [45] numerically analyzed the impacts of Cattaneo-Christov double di usion heat and mass ux models on the transient nano uid ow between two parallel plates with Joule heating and chemical reaction. It is remarked from their study that, the concentration pro le is a decaying function of thermophoresis parameter and increasing function of Brownian motion parameter.…”
Section: Introductionmentioning
confidence: 99%